COMMUNICATION & SUPPORT GROUP THERAPYâ€ DALAM MENGEMBANGKAN POTENSI RESILIENSI REMAJA DARI KELUARGA SINGLE PARENTS - Ummu Salamah (Universitas Garut, 2015)
This research aimed to measured the efficacy of support communication and support group therapy empowering resiliency potentials among adolescent coming from single parents families. This study used case stufy method and the subject of this research were 15 students of SMAN Ciamis. The data was collected using interview and self report and then analyzed using qualitative descriptive analysis. The result reveals that the communication support group therapy has proven successfully enhancing self-concept off all participants. Keywords: Communication, Support Group Therapy and Single Parents